Site Characteristics Checklist of Agricultural Land for Comparison Purposes - Emphasis on Productive Factors:Part I - Mar Iman, Abdul Hamid (Fakulti Ukur dan Harta Tanah, 1990)
In general, the most popular valuation method for smallholdings is the comparison method. This method necessitates comparison of factors contributing to land value, for which data must be collected from ground inspection. In this paper,due attention will be given on some of these factors that constitute site characteristics necessary for the purpose of comparison. The discussion will be divided into two parts. Part I deals with the physical elements of productive factors, mainly soil properties, while Part II with chemical and biological elements.